PENGARUH KECERDASAN EMOSIONAL TERHADAP KINERJA KARYAWAN - Desy Setyorini; Achmad Syahlani (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2018)
This study use a quantitative research method that explains how emotional intelligence affects employee performance. Hypothesis test shows that there is a positive effect of emotional intelligence. Population in this research is all employees of Hotel Pitagiri which total 61 people. From the population, random sampling was taken as 10 people for questionnaire respondent’s. From the results of the research, it can be concluded that there is a positive and significant influence of emotional intelligence on employee performance. The hypothesis of the study states that there is a positive effect of emotional intelligence on employee performance, accepted. This can be known from the results of the data analysis obtained, for the correlation censation test obtained Sig value = 0,000 <0,05 so that the correlation coefficient is significant.